The Role of Mosques as Centers for Social Empowerment and Community Education in Australia - Safiyah (Aafiyah: Jurnal Multidisiplin Ilmu, 2024)
Mosques in contemporary Muslim minority societies no longer function solely as places of worship but also serve as important centers for social empowerment, education, community development, and intercultural interaction. In Australia, mosques play strategic roles in supporting Muslim communities through educational activities, social services, youth development, interfaith dialogue, humanitarian assistance, and cultural integration within multicultural society. This study aims to analyze the role of mosques as centers for social empowerment and community education in Australia and examine their contribution to strengthening social cohesion, religious understanding, and multicultural coexistence. The research employs a qualitative descriptive approach through literature review and contextual analysis of mosque activities, community development, and multicultural social dynamics in Australia. The findings indicate that mosques contribute significantly to religious education, social welfare, youth empowerment, family support, interfaith communication, and the preservation of Muslim identity within minority contexts. However, mosques also face challenges related to Islamophobia, funding limitations, generational differences, social integration, and negative public perceptions regarding Islam. The study emphasizes that strengthening inclusive educational programs, community participation, interfaith collaboration, and social outreach activities is essential for maximizing the positive role of mosques within Australian multicultural society. Therefore, mosques possess strong potential to function as constructive institutions promoting social harmony, education, and community empowerment in contemporary Australia.